An Exploratory Study of Advantages and Disadvantages of Website Preservation - Handisa, Rattahpinnusa Haresariu (Record and Library Journal, 2021)
Background of the study: website preservation should be explored due to several reasons. First, the theme website preservation is classified into a new field so there is a limited number of scientific articles discussing to this topic; Second, website preservation is not an easy task due to its potential challenge. Third, preserving website is an efford to maintain accestability to beneficial resources for future generations. Purpose: This paper will explore benefits and drawbacks in preserving websites. It also discuss problem and solution during website preservation process. The result of discussion will benefit for library manager to formulate an accurate policy on how to maintain accessibility of library’s website. Method: Reviewing literature is an analyses method in this paper Findings: Findings shows that website preservation has a lot of benefits rather than its drawbacks. The website preservation will support humanities researchers to collective memories to special events or importance person in the past; the website preservation assures accesstability to heritage data and it offers opportunity for library to collaborate in developing heritage database. Conclusion: Website preservation will have a lot of benefits rather than drawbacks. Library will be able to develop collective memory for future generations by preserving website contents. In addition, the website preservation also offers efficiency in collecting and managing metadata due to its advance technology.